Dual Directional Expansion of Classical Cepheids in the Small Magellanic Cloud Revealed by Gaia Data Release 3 - Satoya Nakano; Kengo Tachihara (The Astrophysical Journal Letters)
We present the three-dimensional kinematics of classical Cepheids (CCs) in the Small Magellanic Cloud (SMC) using Gaia DR3 data. By crossmatching the CCs obtained from the fourth phase of the Optical Gravitational Lensing Experiment with Gaia DR3, we obtain distances and proper motions (PMs) for 4236 CCs. Among them, radial velocities (RVs) are available for 91 stars, measured by Gaia, enabling the construction of an accurate relationship between distance and RV. Furthermore, we calculate the internal PMs of the CCs, providing the internal dynamics of the SMC while removing the distance projection effects. The CCs exhibit a northeast–southwest distance gradient, with internal PMs pointing northeast for nearer stars and southwest for more distant stars, indicating a northeast–southwest elongation. The RVs of the CCs show a northwest–southeast gradient, consistent with RVs of other stellar populations, and suggesting that the SMC’s northwest–southeast elongation results from interactions with the Large Magellanic Cloud. The distances and RVs of the CCs are nearly uncorrelated, implying that the two elongations arise from distinct causes.